Alazami syndrome: Report of three Indian patients with phenotypic spectrum from adolescence to adulthood. Issue 5 (11th February 2021) - Das, Sweta; Godbole, Koumudi; Abraham, Suneetha Susan Cleave; Ganesan, Paramasivam; Kamdar, Payal; Danda, Sumita
Abstract: Alazami syndrome (ALAZS) (MIM 615071) is a rare autosomal recessive disorder characterized by short stature, dysmorphic facial features, developmental delay, and impaired intellect. It was first reported in a Saudi Arabian family in 2012. Three Indian patients affected with ALAZS, one boy aged 13 years and other two sisters in their 40s are presented. These patients had few unreported dysmorphic facial features: high arched eyebrows and dental overcrowding. No microcephaly was noted in the sisters. One of the sisters did not have short stature. The boy also presented with unilateral buphthalmos of left eye. All three of them have been identified to harbor novel variants in LARP7 .